Nightshade - Albert, Susan Wittig (New York : Berkley Prime Crime, 2008)
China's herb shop and catering business may be thriving, but she's still reeling from her father's death, and not even remotely interested in her half-brother Miles's investigation into that event. China's husband, on the other hand, has no such qualms. And when fate forces her to get involved as well, China realizes it's time to bring the past to light-or else it will haunt her the rest of her life. But China and McQuaid discover that Miles may have been keeping as many secrets as he seemed determined to uncover. How deep do the layers of secrecy go? And who has a stake in concealing the truth after sixteen years? --From amazon.com.
Keywords: Bayles, China (Fictitious character); Women detectives -- Texas; Herbalists; Fathers -- Death -- Psychological aspects; Family secrets; Texas Hill Country (Tex.); Mystery fiction